ON THE MODELS OF FOREIGN LANGUAGE TEACHING (Scientific journal of the Fergana State University, 2023)
The article is devoted to the development and improvement of the foreign language teaching technology, it discusses the various models that have been created to date and are designed to improve the foreign language competences of language learners.